Ocular Manifestation of CACNA1A Pathogenic Variants - Karit Reinson; Katrin Õunap (Pediatric Neurology Briefs, 2016)
Investigators from The Children’s Hospital at Westmead in New South Wales; The Queensland University of Technology in Brisbane; Sydney Children’s Hospital in New South Wales and Laboratoire de Genetique in Paris investigated children with a proven heterozygous missense pathogenic variant in the CACNA1A gene.